2022
DOI: 10.1128/mbio.01794-21
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Control of Metabolic States in Pseudomonas putida by Tuning Polyhydroxyalkanoate Cycle

Abstract: Despite large research efforts devoted to understanding the flexible metabolism of Pseudomonas beyond the role of key regulatory players, the metabolic basis powering the dynamic control of its biological fitness under disturbance conditions remains largely unknown. Among other metabolic hubs, the so-called PHA cycle, involving simultaneous synthesis and degradation of PHAs, is emerging as a pivotal metabolic trait powering metabolic robustness and resilience in this bacterial group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Excess ATP also triggers respiration, but in small cells (such as Bdellovibrio ) the question is whether high ATP levels are incompatible with the maintenance of respiration if the surface of the cell cannot allocate enough respiratory proteins 40 , 41 . In short, PHA defective mutants might have unexpected metabolic consequences 42 46 influencing predation activity, and research in this field could help to identify and eventually overcome predation resistance factors in P. aeruginosa . It is worth noting that the prey range (intra- or interspecies range) does not depend only on the prey susceptibility but also on the predator specificity, which highlights the importance of specific predator–prey susceptibility testing, as their interaction and co-evolution may overcome predation and resistance, respectively 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Excess ATP also triggers respiration, but in small cells (such as Bdellovibrio ) the question is whether high ATP levels are incompatible with the maintenance of respiration if the surface of the cell cannot allocate enough respiratory proteins 40 , 41 . In short, PHA defective mutants might have unexpected metabolic consequences 42 46 influencing predation activity, and research in this field could help to identify and eventually overcome predation resistance factors in P. aeruginosa . It is worth noting that the prey range (intra- or interspecies range) does not depend only on the prey susceptibility but also on the predator specificity, which highlights the importance of specific predator–prey susceptibility testing, as their interaction and co-evolution may overcome predation and resistance, respectively 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, the glyoxylate shunt is inactive during glucose catabolism and its activation was not predicted by the cMCS design ( Supplementary DataFile 2 ( Banerjee et al, 2020 ),). Recent metabolic modeling indicated that preventing PHA formation can lead to glyoxylate shunt activation in P. putida ( Manoli et al, 2022 ). There was a slight (1.1–fold) increase in ED glycolysis flux but major flux rewiring was not found in the cyclic ED-EMP pathway steps.…”
Section: Resultsmentioning
confidence: 99%
“…PHAs are typically synthesized as storage compounds that are accessed under glucose starvation ( Ankenbauer et al, 2020 ) in P. putida and have been previously shown to be closely tied to central carbon metabolism ( de Eugenio et al, 2010a , 2010b ; Escapa et al, 2012 ). Preventing PHA formation in P. putida may be beneficial for indigoidine production because blocking synthesis increases acetyl-CoA and precursor flux through the TCA cycle ( Escapa et al, 2012 ) and has also been predicted to increase ATP production ( Manoli et al, 2022 ). Furthermore, PHA synthesis has been identified as a key component in maintaining energy and redox balance by allowing for dissipation of excess energy ( Manoli et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHA metabolism of bacterial cells is controlled at multiple levels, via nutrient imbalances or stressors, and by specific regulators present in the pha gene cluster [123]. Different bacterial cell growth phases have been studied.…”
Section: Metabolic Pathways Involved In Pha Synthesismentioning
confidence: 99%